If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=3(y-4)
We move all terms to the left:
3-(3(y-4))=0
We calculate terms in parentheses: -(3(y-4)), so:We get rid of parentheses
3(y-4)
We multiply parentheses
3y-12
Back to the equation:
-(3y-12)
-3y+12+3=0
We add all the numbers together, and all the variables
-3y+15=0
We move all terms containing y to the left, all other terms to the right
-3y=-15
y=-15/-3
y=+5
| -2-3x+8x=18 | | -3=r-2r | | -10=-m+3m | | -30=2u=4u | | 4+5-b=-5 | | 4(5x-4)=64 | | 15y+4=94 | | 300+25x=50x | | 0=14-4y | | 7x-8+76=189 | | 15=-5z+2z | | 38=20-x | | 4x-12+2x+8=-15 | | 60/(2-x)=3 | | 5(2x-5)-3=5(x-3)+12 | | (4x+3)(8−3x)=−2x(6x−2) | | 6y-42=8 | | 15+3y^2=0 | | x-80=2x-90 | | 4(m-3=12 | | 4-1+3y^2=0 | | 6(u+2)=2u-12 | | 0=3i-7i | | 5/7-x=1/14 | | 1. 2x–6=0 | | 3w+46=-8(w+8) | | 80+(x+23)=(4x+17) | | 4=4f | | 5=3c–4 | | -8(y-2)=-5y-14 | | -5x-2=30.5 | | -16+32+28+4m=4(16m+4) |